Effective climate action must address both social inequality and inequality aversion - Joël Berger; Ulf Liebe (npj Climate Action)
Abstract While social inequality limits the less affluent’s ability to support climate action, we develop a theoretical framework that analyzes how disadvantageous inequality aversion diminishes motivation for climate cooperation among the broader population. By clarifying how perceptions of disadvantage or social injustice can harm climate cooperation or produce backlash, we derive tailored countermeasures to enhance climate cooperation.